Dari Pembelajar Menjadi Tutor: Perkembangan Identitas Profesional Alumni Teaching Clinic di Pare - Efriswan Situmorang; Farida Repelita Waty Kembaren (Universitas Muhammadiyah Surabaya, 2026)
Teacher professional development (TPD) in English language teaching often remains theory-oriented, leaving novice teachers insufficiently prepared for practical classroom demands. This study explores how participation in the Teaching Clinic (TC) program contributes to the professional development of English tutors in Pare, Indonesia. Using an interpretative phenomenological analysis (IPA) approach, the research examines how alumni interpret their transition from language learners to professional tutors. Three TC alumni who had completed the ten-month training program and had at least six months of tutoring experience were purposively selected. Data were collected through two rounds of semi-structured interviews and supported by document analysis of lesson plans, teaching materials, and reflective journals. The findings indicate that tutor development is shaped by intensive learning routines, peer-supported learning communities, mentoring relationships, and feedback-rich teaching practice. Professional identity becomes stronger when participants begin to perceive teaching as a responsibility toward learners rather than merely a process of improving their own language skills. The study highlights the value of practice-based training in supporting tutor development while also identifying the need for further development in academic English and digital pedagogy.